Developing speaking approaches in teaching ESP - Shadmanov Sherzod Xursanaliyevich (Researchparks Publishing, 2023)
The object of this article is to make an in-depth study of the English language teaching, particularly, speaking skills. The article gives a brief overview of the substance of the topic and its importance today.